Nutrient accumulation in Brassica: identification of new targets for crop improvement and biofortification - Alcock, Thomas David (2019)
Plants require at least 14 essential mineral nutrients in order to successfully complete their life cycle. Nitrogen, phosphorus and potassium are required in particularly large quantities, and there is an ever increasing demand for fertiliser inputs to maintain adequate concentrations in crops. Humans are made up of at least 35 mineral nutrients, most of which originate from the ingestion of plant material. It is likely that much of the world’s population consumes insufficient quantities of numerous mineral nutrients, including calcium and magnesium.